PENGARUH ADOPSI IFRS TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MENUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2010-2014 - Deni Wijanarko; Achmad Tjahjono (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2016)
The purpose of this research is to determine the effect of the adoption of IFRS on earnings management is measured by three proxy smothing income, differentials change in net income (ΔNI), ratio of the middle of the difference changes the net income in the difference in the change in operating cash flow (ΔCF) and the correlation between the accrual and cash flow. In this study also uses control variables to capture whether there are other influences that different areas: size, leverage, growth and ROE. The population of this research is all manufacturing companies listed in Indonesia Stock Exchange 2010-2014. Sampling technique in this research is purposive sampling. Samples are 36 companies with a total of as many as 180. The sample observation method of data analysis used is multiple regression analysis. The results showed that there are significant adoption of IFRS on earnings management with significant value 0.023 <0.05. Variable control of size, leverage and ROE affect the behavior of managers in performing earnings management practices with significant value size = 0,030, leverage = 0.000 ROE = 0.014 (<0.05). While the growth control variables do not affect managers in earnings management practices.